2021
DOI: 10.21043/malia.v5i2.11800
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Relationship Marketing, Experential Marketing and Sharia Marketing Characteristics on Customer Loyalty of Sharia Bank With Customer Satisfaction as Intervening Variable

Abstract: Loyalty is a consumer's commitment to a business model that can be in the form of a brand, store, and/or supplier due to several things that cause consumers to make long-term purchases. The data was obtained from the distribution of questionnaires by researchers to respondents. Samples were taken as many as 100 respondents. Data collection techniques by non-probability sampling. The data obtained were then processed using the SPSS20 tool. This research uses quantitative research by using multiple linear regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
2
1
1
Order By: Relevance
“…The results of this study are in line with research conducted by Khoiri & Adityawarman ( 2021) customer satisfaction has a positive effect on customer loyalty. In contrast to research conducted by Priantoro & Yudiana, (2021) which states that satisfaction has no positive and significant effect on customer loyalty.…”
Section: The Influence Of Customer Satisfaction On Customer Loyaltycontrasting
confidence: 82%
“…The results of this study are in line with research conducted by Khoiri & Adityawarman ( 2021) customer satisfaction has a positive effect on customer loyalty. In contrast to research conducted by Priantoro & Yudiana, (2021) which states that satisfaction has no positive and significant effect on customer loyalty.…”
Section: The Influence Of Customer Satisfaction On Customer Loyaltycontrasting
confidence: 82%
“…Studies state that in the service industry, especially health, customer value positively affects consumer loyalty. In the research conducted by Priantoro & Yudiana (2021) looking at the influence of tourist value co-creation behavior on destination loyalty mediated by perceived value. It was found that the variable tourist cizenship behavior, which is a dimension of value co-creation behavior, has an influence on destination loyalty as an extra role behavior.…”
Section: Hypothesismentioning
confidence: 99%
“…Dari segi teknis, loyalitas dapat tumbuh melalui pendekatan persuasif yang mendorong dan memperluas sikap berpikir positif serta perilaku positif. Tjiptono dalam (Priantoro & Yudiana, 2021) Peran loyalitas adalah menciptakan harmoni dalam hubungan antara pemikiran dan tindakan. Loyalitas menitikberatkan pada pola pembelian konsumen, seperti partisipasi dalam promosi dan kemungkinan terjadinya pembelian.…”
Section: Teori Loyalitasunclassified